Implementasi Pengawasan Akta Notaris Oleh Dewan Kehormatan Daerah Kota Bandar Lampung - Abdullah, Ali; Barus, Zulfadli; Eka Putri, Pritie Anissa (Universitas Sang Bumi Ruwa Jurai, 2025)
According to the Central Honorary Council of the Indonesian Notaries Association Regulation Number 1 of 2017 Article 2 regarding the daily creation of deeds, it is stated that the Reasonable Limit for the creation of deeds by a Notary as a member of the Association is 20 (twenty) deeds per day. The results of this study show that PerPDK INI Number 7 of 2017 concerning the Reasonable Limit on the Number of Deeds Created Per Day is adequate; however, in practice, the implementation of the regulation on the ground is not effective, as some Notaries still create more than 20 (twenty) deeds per day. This is based on Article 2 of PerPDK INI Number 7 of 2017, which also explains that as long as it can be accounted for, a Notary may exceed the limit of 20 deeds per day as long as it is justifiable. The implementation of PerPDK INI Number 7 of 2017 regarding the Reasonable Limit on the Number of Deeds Created Per Day involves ambiguities that lead to misinterpretation of Article 2 Paragraphs (1) and (2) by Notaries, as well as weak supervision due to the reluctance to reprimand and report among Notaries. The legal consequences of this issue are that the relevant deeds only have the evidentiary power of private deeds for the parties involved, and the failure to fulfill the obligation to read the deed in front of the parties creates the potential for Notaries to face sanctions